Efek Protektif Ekstrak Jahe Merah (Zingiber officinale var. rubrum) Terhadap Sel Spermatogenik, dan Sel Leydig pada Mencit yang Diinfeksi Staphylococcus aureus secara Intra Uretra - Sukarjati; Nur Asiah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2026)
Infections of the male genital tract can cause infertility in up to 15% of cases. Staphylococcus aureus (S. aureus) is a pathogenic bacterium that can significantly contribute to infertility. Red ginger (Zingiber officinale var. rubrum) contains active compounds such as gingerol, shogaol, zingerone, and flavonoids, which have the potential to exert protective effects against testicular tissue damage caused by infection. This study aimed to evaluate the effect of red ginger on spermatogenic cells in mice infected intraurethrally with S. aureus. A total of 30 male mice aged 3 months were used and divided into three groups, with 10 mice in each group: A; control group, B; group infected intraurethrally with S. aureus, and C; group infected with S. aureus and treated with red ginger extract. The results showed a significant effect (p ≤ 0.05) of red ginger extract administration on the number of spermatogonia, spermatocytes, spermatids, Leydig cells, and testicular weight in mice infected with S. aureus intraurethrally. Therefore, red ginger extract can inhibit the growth of S. aureus and improve spermatogenic cell condition in mice affected by S. aureus infection.   Keywords: S.aureus; genital tract infection, spermatogenic cells, red ginger (Zingiber officinale   var. rubrum)